HALAL TOURISM VILLAGE DEVELOPMENT MODEL: A CASE STUDY OF NATURAL AND CULTURAL TOURISM OBJECTS IN TASIKMALAYA REGENCY - Akbar Rizqi Kurniawan; Feni Mustika Sari; Moch. Fajar Deliaz (RADJA PUBLIKA, 2025)
Halal tourism is a growing segment in line with the increasing demand of Muslim tourists for tourism products that comply with sharia principles. In Tasikmalaya Regency, the potential of natural tourism objects (e.g., Cikaso Waterfall, Protected Forest Areas) and cultural heritage (e.g., Songket Crafts, Traditional Ceremonies) have not been optimally synergized within the framework of halal tourism, especially at the village level. This study aims to formulate a model for developing halal tourism villages that integrates natural, cultural, and halal standards, and to provide policy recommendations for local governments and stakeholders. The method used is qualitative research with a desk - study approach. Secondary data were collected from: (1) scientific journals and proceedings related to halal tourism; (2) reports from BPS, the Tasikmalaya Regency Tourism and Culture Office, and policy documents (regional regulations, halal standards from the Indonesian Ulema Council (MUI), and the Indonesian Food and Drug Authority (LPPOM); (3) publications from research institutions and Islamic tourism organizations. Content analysis was conducted thematically, using a coding scheme that includes: policy, infrastructure, halal certification, natural potential, cultural values, and the role of stakeholders. Triangulation of data sources ensures the validity of the findings. The research results are expected to produce a five-dimensional conceptual model (Policy & Regulation, Infrastructure & Facilities, Halal Certification, Natural - Cultural Potential, Community Participation) that can be used as a guideline for villages in Tasikmalaya to develop sustainable halal tourism products. This model also provides insight into the driving and inhibiting factors, as well as strategies for establishing a community-based halal tourism ecosystem. The contributions of this research include: (a) enriching the literature on halal tourism villages in Indonesia; (b) providing a practical framework for regional policymakers; (c) offering a basis for local business actors in utilizing natural and cultural potential in a sharia - friendly manner.